Belgische Grafik der Gegenwart. - Rodekamp, Volker (Bielefeld : Karl Kerber Verlag, 1993)
Alechinsky ; Belgeonne ; Bury ; De Keyser ; Delahaut ; Duchateau ; Dewint ; Hoorne ; Masereel ; Panamarenko ; Raveel
boek